Association between the presence of a 38 kDa factor in the seminal plasma and inhibition of sperm motility in jundiá fish Rhamdia quelen - Campos, Vinicius Farias (2010)
Protein factors have been identified in the seminal plasma of fish and mammal species and, in some situations, associated to sperm quality indicators. However, for jundiá fish (Rhamdia quelen), such factors and those potential associations remain unknown. In the present study, we aimed to identify some protein factors present in the seminal plasma of jundiá fish and to evaluate their association to sperm motility. SDS-PAGE was used to identify 14 bands, with molecular weight ranging from 217.1 to 7.1 kDa. Sperm motility was evaluated for 21 males. Four protein bands(81.5; 60.4; 33.6; and 25.5 kDa) were present in all seminal plasma samples. One protein band with molecular weight of 38.3 kDa was associated to reduced sperm motility of jundiá (P<0.01), since it was detected in 91.4% of the samples having motility lower than 80%. These results suggest that this seminal protein band associated to lower sperm motility may be considered a potential biochemical marker for sperm quality.